The Strategy of Translating Idioms between Kurdish and Persian/Farsi - Qasim, Huda Abdulqader; Rajab, Sleiman Ismail (Journal of Duhok University, 2019)
This research deals with translation strategies of idioms in Kurdish and Persian. The research followed the descriptive comparative approach. The two languages are similar since there is a lexical approach between then. There are a number of common idioms and expressions including idiomatic expressions since such expressions have a cultural characteristic. Thus, there are differences between the two languages in terms of idiomatic expressions. This study focuses on translating idiomatic expressions from Kurdish into Persian to explore and clarify some aspects. It discusses the concept of idiomatic expressions equivalence translation and problems and difficulties of translating idiomatic expressions. With the use of illustrative examples the research tackles the strategies used in translating idiomatic expressions between Kurdish and Persian.